CogRadNet: Ubiquitous heterogeneous wireless networks - Omar, Mohd Hasbullah; Hassan, Suhaidi; Mohd Shabli, Ahmad Hanis (School of Engineering, Taylor’s University College, 2009)
Mobile radio systems have shown rapid growth and hence increase the awareness for more efficient use of spectrum. With the advancements of technology, the development of radio systems that is dynamic and efficient in terms of spectrum usage can be realized. Cognitive radio system is one of the advancement that enhanced the adaptive capabilities of the systems that make the usage of spectrum more efficient, versatile and flexible. It also able to adapt their operations based on its internal and external factors by sensing its environment. The cognitive radio systems may be a solution for the spectrum scarcity faced by developer to tackle the issue of signal propagation and bigger coverage for broadband internet access. This paper will addressed the cognitive radio technology for ubiquitous broadband wireless internet access.